2020
DOI: 10.4271/2020-01-0610
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Lubricant and Fuel Composition on LSPI and Emissions in a Turbocharged Gasoline Direct Injection Engine

Abstract: <div class="section abstract"><div class="htmlview paragraph">Downsized turbocharged gasoline direct injection (TGDI) engines with high specific power and torque can enable reduced fuel consumption in passenger vehicles while maintaining or even improving on the performance of larger naturally aspirated engines. However, high specific torque levels, especially at low speeds, can lead to abnormal combustion phenomena such as knock or Low-Speed Pre-Ignition (LSPI). LSPI, in particular, can limit furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The authors also found that decreased LSPI severity corresponded with increased octane numbers and higher ethanol content of the market fuels. A number of published studies have investigated fuel lubricant interactions on LSPI [46][47][48]. Hu et al [46] found that the properties of oil particles entering the engine cylinder were significantly affected by fuel dilution.…”
Section: Low Speed Pre-ignitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also found that decreased LSPI severity corresponded with increased octane numbers and higher ethanol content of the market fuels. A number of published studies have investigated fuel lubricant interactions on LSPI [46][47][48]. Hu et al [46] found that the properties of oil particles entering the engine cylinder were significantly affected by fuel dilution.…”
Section: Low Speed Pre-ignitionmentioning
confidence: 99%
“…As expected, the combination of a high LSPI activity fuel and a high LSPI activity lubricant resulted in large numbers of LSPI events. Kar et al [48] found that the oil composition had a strong impact on LSPI frequency and that LSPI frequency could be reduced by changing the lubricant formulation. In addition, it was found that fuels blended with high polyaromatic content increased LSPI frequency significantly and also caused a significant increase in particulate mass and particulate number emissions.…”
Section: Low Speed Pre-ignitionmentioning
confidence: 99%
“…The authors also found that decreased LSPI severity corresponded with increased octane numbers and higher ethanol content of the market fuels. A number of published studies have investigated fuel lubricant interactions on LSPI [42][43][44]. Hu et al [42] found that the properties of oil particles entering the engine cylinder were significantly affected by fuel dilution.…”
Section: Low Speed Pre-ignitionmentioning
confidence: 99%
“…As expected, the combination of a high LSPI activity fuel and a high LSPI activity lubricant resulted in large numbers of LSPI events. Kar et al [44] found that the oil composition had a strong impact on LSPI frequency and that LSPI frequency could be reduced by changing the lubricant formulation. In addition, it was found that fuels blended with high polyaromatic content increased LSPI frequency significantly and also caused a significant increase in particulate mass and particulate number emissions.…”
Section: Low Speed Pre-ignitionmentioning
confidence: 99%
“…Using modified inlet components design [19], developed TC such as Variable Geometric Turbines (VGT) [20] and twin-turbines [21], improved injection strategy [22], water injection [23], employing additives [24], combined [25] and alternative [26] fuels, Exhaust Gas Recirculation (EGR) [27], and electrified components [28] are considered as the some of these techniques. It is asserted that both fuel economy and đ¶đ‘‚ 2 production rate are noticeably improved during these efforts, but some challenging issues such as knock [29] and super-knock [30], Low-Speed Pre-Ignition (LSPI) [31], and weak performance especially at low-speed regions [32] are the main obstacles which researchers try to cope with them. Indeed, to achieve the ultra-emission reduction goal, the efforts lead to the usage of Compressed Natural Gas (CNG) as the fuel of downsized engines [33][34][35].…”
Section: Introductionmentioning
confidence: 99%